Findings from an expert focus group on psychotropic medication deprescribing practices for children and youth with complex needs - Theall, Laura; Ninan, Ajit; Currie, Melissa (Frontiers in Child and Adolescent Psychiatry, 2024)
Psychotropic medication can be effective at stabilizing emotional and behavioural disturbances associated with physiological processes in children and youth. When medication benefits, indication or adverse effects are queried, deprescribing should be considered. Current guidelines for deprescribing are mainly for adults/elderly and largely theoretical, not practical, especially for polypharmacy. At a tertiary center for children and youth with complex emotional and behavioural needs, physicians on staff have expertise in conducting assessments of medication efficacy, side effect burden, and safety concerns. Deprescribing is routinely undertaken in the context of inpatient and outpatient services in partnership with children/youth and their families. A qualitative initiative leveraged the specialized deprescribing expertise of eight physicians (six psychiatrists and two pediatricians). Emerging themes were medication review, timing, a stepwise approach, and setting conditions (inpatient and outpatient), with recurring subcategories of patient/family engagement as well as the underlying importance of continuity of care with psychosocial/behavioural supports. The findings from this expert focus group serve as a step towards supporting prescribing clinicians in mindful deprescribing when medications are no longer in the best interest of young patients.